2017
DOI: 10.1016/j.fertnstert.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oocyte vitrification on embryo quality: time-lapse analysis and morphokinetic evaluation

Abstract: The embryo quality of vitrified oocytes was not impaired: cc2, quality according to our hierarchic morphokinetic model, and implantation rates were similar between fresh and vitrified oocytes. However, morphokinetic differences were observed from t2 to tB. Our main study limitation was the retrospective nature of the analysis, although a large database was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 40 publications
2
22
0
2
Order By: Relevance
“…The procedures for in vitro fertilization (IVF) and embryo culture did not have any difference between cryopreserved/warmed oocytes and fresh oocytes. However, recently, it has been found by time-lapsing analysis and morphokinetic that cryopreserved/warmed oocytes had about 1 h of delayed fertilization and embryo development [5]. Delayed embryo development is very often in human IVF even fresh oocytes are used, which is indicated by a delayed blastocyst formation.…”
Section: Introductionmentioning
confidence: 99%
“…The procedures for in vitro fertilization (IVF) and embryo culture did not have any difference between cryopreserved/warmed oocytes and fresh oocytes. However, recently, it has been found by time-lapsing analysis and morphokinetic that cryopreserved/warmed oocytes had about 1 h of delayed fertilization and embryo development [5]. Delayed embryo development is very often in human IVF even fresh oocytes are used, which is indicated by a delayed blastocyst formation.…”
Section: Introductionmentioning
confidence: 99%
“…So far, few studies have been published on the morphokinetic behaviour of embryos derived from vitrified-warmed oocytes in comparison with fresh oocytes. There is thought to be only one study that has reported data on the kinetics from embryos derived from vitrified oocytes up to the blastocyst stage and although this report included a large cohort of treatments, the study was not performed on sibling oocytes (Cobo et al, 2017). In the present study, although small in its sample size, time-lapse analysis up to the blastocyst stage was analysed and revealed an overall delay in embryo development from the time of PN fading (tPNf) up to the time of blastulation in the VITO compared with the FSHO.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that this type of embryo quality assessment is prone to inter-observer variations. The introduction of timelapse imaging has shown that embryo development is a very dynamic process and that several critical developmental stages can go unnoticed with the use of traditional morphological assessment (Basile et al, 2015;Cobo et al, 2017;Meseguer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unknown if this may translate to pregnancy or neonatal outcomes. 29 Another recent change in practice is that transfer of day 5 embryos has been advocated by ASRM to decrease the risk of multiple gestations and allow selection of the highest quality embryo. 30 The development of the embryo to the blastocyst stage provides an additional competence measure, as the activation of the embryonic genome occurs at the 8-cell stage.…”
Section: Evolving Technologiesmentioning
confidence: 99%